Peranan Masyarakat Mengangkat Perekonomian Kampung Kumuh Berbasis Kampung Ramah Lingkungan Sebagai Bagian Untuk Dijadikan Sebagai Desa Wisata - Erni Prasetiyani (Institut Ilmu Sosial dan Manajemen STIAMI, 2020)
Identical slums with residents far from the word prosperous and uneducated. Slums have become a common sight of densely populated cities that are urbanites. The Green Village program issued by the Bogor district as a form of concern for the environment of the population which is fairly dense and slum population due to lack of greening land and lack of awareness of environmental cleanliness. The research method used is qualitative. Kampung Gunung Geulis Bogor is one of the villages that has changed the paradigm from a slum village to an Eco-friendly Village (KRL). Residents receive education about the importance of greening and environmental cleanliness by forming a waste bank and recycling waste into useful products. From KRL, the population is able to produce compost and plant crops with used media. Compost and plants are currently consumed by themselves to meet the needs of residents. The excess production has the potential to be sold in the market as additional income for citizens. This target is a long-term program so that citizens will prosper independently. In addition raising the economy of the citizens, KRL creates this village as an alternative tourism village in Kabupaten Bogor.